Effects of inoculation with tropical rice associative N2-fixing bacteria Azospirillum brasilense NO40 in the red paddy soil - FANG Ping; ZHANG Li-mei; JIA Xiao-ming; M N A Omar (浙江大学学报. 农业与生命科学版)
Effects of inoculation with Azospirillum brasilense NO40 isolated from Egypt on rice growth and yields under different nitrogen fertilizer levels were investigated at Dongyang county of Zhejiang province. The results showed that the counts of colony grown on nitrogen-free medium isolated from rice rhizosphere and root were increased by inoculating with NO40 in contrast to the control, irrespective of the nitrogen fertilizer levels and rice growing periods. It was found that the plant height, chlorophyll content of the newly developed rice leaves were significantly increased after inoculating with NO40.